CAPACITY BUILDING OF KENYAN HEALTH WORKERS IN PPH PREVENTION AND MANAGEMENT: SAVING MORE PARTURIENT LIVES (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2022)
Introduction: Despite being largely preventable, postpartum hemorrhage (PPH) is the modal cause of  maternal mortality globally and in Kenya.  Methodology: During the 44th Annual Scientific Congress of the Kenya Obstetrical and Gynecological  Society, a 2-day PPH workshop was held in Msambweni Sub-District Hospital in Kwale County to identify  addressable gaps and to build local capacity. The participants sat a uniform pre- and post- test and evaluated  the course. Results: The modal cadres present were clinical officer interns (8) and midwives (7). Out of the 28  participant responses analyzed, the pretest revealed low average level of knowledge (43.8%), with  devascularization (31.8%) and resuscitation (39.7%) showing the lowest levels. The post-test revealed  substantial improvement in overall average knowledge that was attributable to the training (75.2%,  p=0.001). Three quarters of the participants rated the training as excellent, while a fifth rated the training as  good.  Discussion: PPH is known to be the most significant cause of maternal mortality. However, knowledge of  its prevention, diagnosis and management were poor. The training resulted in significant improvement in  knowledge, while the use of high-fidelity simulation drills enhanced emergency preparedness. Conclusion: Overall, there is a significant role for capacity building through in-service trainings. There  is therefore a need to scale-up such trainings in order to further reduce contribution of PPH to maternal  mortality in Kenya.